Technical details of thoracic endovascular aortic repair with fenestrations for thoracic aortic pathologies involving the aortic arch: A Chinese expert consensus - Qiu, Chenyang; Li, Zhenjiang; Dai, Xiangchen; Lu, Xinwu; Lu, Qingsheng; Li, Xiaoqiang; Zhou, Weimin; Guo, Pingfan; Pan, Jun; Li, Donglin; Wu, Ziheng; Zhang, Hongkun (Frontiers in Cardiovascular Medicine, 2022)
Thoracic aortic pathologies involving the aortic arch is a great challenge for vascular surgeons. Maintaining the patency of supra-aortic branches while excluding the aortic lesion remains difficult. Thoracic endovascular aortic repair (TEVAR) with fenestrations provides a feasible and effective approach for such disease. The devices needed in the procedure are off-the-self, with promising results reported in many centers. Up to now, there is no guideline exclusively focusing on the technique details of TEVAR with fenestrations. Experts from China have discussed the technical parts of both in suit fenestrations (needle and laser) and fenestrations in vitro (direction inversion strategy and guidewire-assisted strategy), providing a technical reference, with the aim to standardize the procedure and improve the outcomes.